Anisotropic extension of the Kohler–Chao–Tikekar cosmological solution with like Wyman IIa complexity factor - B. Siza; J. Andrade; D. Santana; Tayyab Naseer (European Physical Journal C: Particles and Fields)
Abstract We construct a new stellar compact object model in the regime of anisotropic pressure using the framework of gravitational decoupling via minimal geometric deformation, with the particularity that the seed solution used is the known Kohler–Chao–Tikekar cosmological solution. As an extra condition to close the Einstein’s field equations resulting for this construction, we use a generalised complexity factor for self-gravitating spheres to the well-known Wyman IIa solution. The resulting model fulfils the fundamental physical acceptability stellar conditions for a compactness factor of a pulsar SMC X-1. The stability of the model is also investigated.